2022
DOI: 10.17582/journal.aavs/2023/11.1.150.158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Guava Filtrate Supplementation in Tris and Citrate-Based Extenders on Spermatozoa Quality of Brangus Bull after Sex-rest

Abstract: The objective of this study was to determines the effect of guava fruit filtrate (GF) supplementation in Tris and Citrate-based extenders on spermatozoa quality of Brangus bull after sex-break. Semen samples (twelve ejaculates) were diluted in Tris-egg yolk (TEY) without GF (control group, T1), TEY with 10% GF (T2), Citrate-egg yolk (CEY) with 10% GF (T3), Citrate with 10% egg yolk and 10% GF (T4), then chill-storage. The variables quality evaluated include spermatozoa progressive motility, visibility, and abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Sugarcane juice combined with egg yolk was very good at maintaining abnormal spermatozoa (Mahfud et al, 2019). The benefits of egg yolk were found in lipoprotein and lecithin, which played a role in maintaining and protecting the intensity of the lipoprotein sheath and spermatozoa cells from decreasing temperature and stabilizing the plasma membrane (Sumadiasa et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sugarcane juice combined with egg yolk was very good at maintaining abnormal spermatozoa (Mahfud et al, 2019). The benefits of egg yolk were found in lipoprotein and lecithin, which played a role in maintaining and protecting the intensity of the lipoprotein sheath and spermatozoa cells from decreasing temperature and stabilizing the plasma membrane (Sumadiasa et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The smell of collected semen in this study was typical, which indicated normal semen with an absence of contamination. Sumadiasa et al (2022) stated that normal semen has a distinctive fishy odour accompanied by the smell of the animal. However, a foul odor can occur when the semen contains pus caused by an infection of male reflux organs (Lopes, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation